Activation of Pyk2 by CaM kinase II in cultured hypothalamic neurons and gonadotroph cells. Issue 5 (11th November 2018) - Okitsu‐Sakurayama, Shiho; Higa‐Nakamine, Sayomi; Torihara, Hidetsugu; Takahashi, Hana; Higashiyama, Shigeki; Yamamoto, Hideyuki
Abstract: Gonadotropin‐releasing hormone (GnRH) is secreted from hypothalamic GnRH neurons and stimulates a GnRH receptor in gonadotroph cells and GnRH neurons. The GnRH receptor belongs to the G‐protein‐coupled receptors, and stimulation of the GnRH receptor activates extracellular signal‐regulated protein kinase (ERK). We reported previously that the δ2 isoform of Ca 2+ /calmodulin‐dependent protein kinase II (CaM kinase IIδ2) was involved in GnRH‐induced ERK activation in cultured GnRH neurons (GT1–7 cells). Recently, we found that GnRH treatment of GT1–7 cells activated proline‐rich tyrosine kinase 2 (Pyk2), and Pyk2 was involved in ERK activation. In the current study, we examined the possibility that CaM kinase IIδ2 might activate Pyk2. Knockdown of CaM kinase IIδ2 and KN93, an inhibitor of CaM kinases, inhibited the GnRH‐induced activation of Pyk2. In the case of cultured gonadotroph cells (αT3‐1 cells), knockdown of CaM kinase IIβ'e inhibited GnRH‐induced Pyk2 activation. In addition, our inhibitor studies indicated that Pyk2 and CaM kinase II were involved in the GnRH‐induced shedding of proHB‐EGF in GT1–7 cells. These results suggested that CaM kinase II activated the ERK pathway through Pyk2 activation and HB‐EGF production in response to GnRH. Abstract : We found that Ca 2+ /calmodulin‐dependent protein kinase II (CaM kinase II) activated proline‐rich tyrosine kinase 2 (Pyk2) in cultured gonadotropin‐releasing hormone (GnRH) neurons and gonadotroph cells. In addition, our inhibitor studies indicated that Pyk2 and CaM kinase II were involved in the GnRH‐induced shedding of proHB‐EGF. Our results suggested that CaM kinase II activated the ERK pathway through Pyk2 activation and HB‐EGF production in response to GnRH.